Active cell balancing of Li-Ion batteries using single capacitor and single LC series resonant circuit - Ferdous S. Azad; A. K. M. Ahasan Habib; Abidur Rahman; Istiak Ahmed (Institute of Advanced Engineering and Science, 2020)
In this paper a novel single series resonant tank and capacitor converter based voltage balancing circuit for series supercapacitor string and battery cells string is presented. It recognizes the balancing circuit which recovered the maximum energy and zero voltage gap between cells in a series supercapacitor system or battery system. This balancing circuit not only inherits the improvement of conventional single series resonant converter based balancing system, but also recovers the drawback of switching loss, conduction loss and voltage gap between cell strings. All MOSFET switches are controlled by a pair of complementary PWM signals. Also the resonant tank and parallel capacitor operate between the two mode of charging and discharging. This voltage balancing circuit has shown promising result to be used in battery management system.